2003
DOI: 10.1161/01.str.0000050661.67548.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hyperhomocysteinemia on the Neurovascular Coupling Mechanism in Healthy Young Adults

Abstract: Background and Purpose-Hyperhomocysteinemia is a vascular risk factor that infers with the nitric oxide signaling pathway of endothelial vasoregulation. Most investigations in young healthy humans on the peripheral vasculature using a standardized methionine challenge demonstrated altered vascular reactivity. In contrast, the cerebral autoregulation mechanism was shown to be unaffected by the same methionine load. To obtain additional insight into the compensatory range of the cerebral vasculature during a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…The initial temporal pattern of CBFv response, involving a steep bilateral increase, is consistent with former TCD studies using a broad variety of brain activation paradigms (4,14,15,22,24,29,30,32,37). In keeping with our results, Duscheck et al (15) found the effects of BP on CBFv responses during arithmetic processing were also more pronounced during the first second of the response.…”
Section: Discussionsupporting
confidence: 92%
“…The initial temporal pattern of CBFv response, involving a steep bilateral increase, is consistent with former TCD studies using a broad variety of brain activation paradigms (4,14,15,22,24,29,30,32,37). In keeping with our results, Duscheck et al (15) found the effects of BP on CBFv responses during arithmetic processing were also more pronounced during the first second of the response.…”
Section: Discussionsupporting
confidence: 92%
“…However, this finding is in agreement with previous results of the change in cerebral blood flow velocities after a standardized methionine challenge. Rosengarten and colleagues reported that although homocysteine levels increased significantly after a methionine loading, no significant changes were observed in the resting cerebral flow velocities [11]. It is known that the cerebral vasculature differs in many functional and morphological aspects from the peripheral vasculature, having a wider compensatory range to maintain adequate blood flow than peripheral vasculature [11].…”
Section: Discussionmentioning
confidence: 99%
“…Rosengarten and colleagues reported that although homocysteine levels increased significantly after a methionine loading, no significant changes were observed in the resting cerebral flow velocities [11]. It is known that the cerebral vasculature differs in many functional and morphological aspects from the peripheral vasculature, having a wider compensatory range to maintain adequate blood flow than peripheral vasculature [11]. This compensatory capacity of cerebral vasculature may result in no gross alteration of cerebral blood flow velocities and PI even after increased serum homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have identified a strong, independent and doserelated association between elevated Hcy levels and vascular diseases, including stroke (11)(12)(13)(14)(15)(16)(17)(18). The exact mechanisms responsible for this association is still under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction is hypothesized to be caused by the potency of Hcy to interfere with the action of endothelial vasodilators such as NO (14). It is postulated that NO is scavenged by superoxide anion generated in the metabolic pathway of Hcy (16). When NO formation is reduced, excessive Hcy may further damage the endothelium by generation of ROS (15,17), thereby increasing lipid peroxidation (18).…”
Section: Introductionmentioning
confidence: 99%